Effect of Penalty Minute Rule Change on Injuries and Game Disqualification Penalties in High School Ice Hockey. Issue 2 (February 2019) - Kriz, Peter K.; Staffa, Steven J.; Zurakowski, David; MacAskill, Matthew; Kirchberg, Tyler; Robert, Kyle; Baird, Janette; Lockhart, Greg
Background: Recent efforts have focused on eliminating dangerous hits in ice hockey. Fair play rule changes have successfully reduced injury risk but have not been widely implemented. Purpose: To determine the effect of a penalty infraction minutes (PIM) rule change in high school boys' ice hockey on injuries and game disqualification penalties. Study Design: Cohort study; Level of evidence, 3. Methods: Injury data were collected from 2 Rhode Island hospital systems and game/penalty data through the Rhode Island Hockey Coaches Association website. Participants included high school boys' hockey varsity players aged 13 to 19 years presenting to 5 emergency departments for hockey injuries during 6 seasons (December 2012–April 2018). Rule change for the 2015-2016 season implemented varying suspensions for players accumulating ≥50 PIM and ≥70 PIM during regular season and playoffs. Injuries were classified as body checking or non–body checking related, and injury rates pre– versus post–rule change were compared via the Cochran-Mantel-Haenszel chi-square test with the odds ratio (OR) to measure risk reduction. Results: During the study period, 1762 boys' high school varsity hockey games were played. Of 134 game-related injuries, 82 (61.2%) were attributable to body checking. The PIM rule change was associated with a significant reduction in all injuries (OR, 0.55; 95% CI, 0.35-0.86; P = .008), concussion/closed head injury (OR, 0.44; 95% CI, 0.23-0.85; P = .012), and combined subgroups of concussion/closed head injury and upper body injury (OR, 0.50; 95% CI, 0.31-0.80; P = .003). Game disqualification penalties per season were not significantly reduced following the rule change, occurring in 5.2% of games before the rule change and 4.4% of games after (OR, 0.84; 95% CI, 0.54-1.31; P = .440). Conclusion: Implementation of a statewide PIM restriction rule change effectively reduced the mean number of game-related injuries per season among high school boys' hockey varsity players.